Political openness and heritage processes in Belo Horizonte: reflections from a life trajectory (Patrimônio e Memória, 2017)
The aim of this article is to analyze the heritage policies of Belo Horizonte, during the democratization period in Brazil, through the use of life trajectory as a methodological resource. Through the professional career of the director of a museum in Belo Horizonte it sought to understand how the cultural policies of the city are structured. In other words, starting out from the director’s professional experience, it tried to cover up the structures that organize the heritage policies in the Minas Gerais capital. Thus, with its own construction of narrative, it was possible to establish a direct relationship between political opening and heritage processes.
Keywords: Trajectory; Culture; Heritage